Benznidazole and amiodarone combined treatment attenuates cytoskeletal damage in Trypanosoma cruzi-infected cardiac cells - Barbosa, Juliana Magalhães Chaves; Pedra-Rezende, Yasmin; Pereira, Luíza Dantas; de Melo, Tatiana Galvão; Barbosa, Helene Santos; Lannes-Vieira, Joseli; de Castro, Solange Lisboa; Daliry, Anissa; Salomão, Kelly (Frontiers in Cellular and Infection Microbiology, 2022)
Chagas disease (CD), a neglected tropical disease caused by the protozoan parasite Trypanosoma cruzi, is an important public health problem mainly in Latin America, leading to approximately 12,000 annual deaths. Current etiological treatment for CD is limited to two nitro compounds, benznidazole (Bz) and nifurtimox (Nif), both presenting relevant limitations. Different approaches have been employed to establish more effective and safer schemes to treat T. cruzi infection, mostly based on drug repurposing and combination therapies. Amiodarone (AMD), an antiarrhythmic medicament of choice for patients with the chronic cardiac form of CD, is also recognized as a trypanocidal agent. Therefore, our aim is to investigate the combined treatment Bz + AMD on trypomastigote viability, control of T. cruzi intracellular form proliferation, and recovery of the infection-induced cytoskeleton alterations in cardiac cells. The combination of Bz + AMD did not improve the direct trypanocidal effect of AMD on the infective blood trypomastigote and replicative intracellular forms of the parasite. Otherwise, the treatment of T. cruzi-infected cardiac cells with Bz plus AMD attenuated the infection-triggered cytoskeleton damage of host cells and the cytotoxic effects of AMD. Thus, the combined treatment Bz + AMD may favor parasite control and hamper tissue damage.